The Influence of Mental Health on Employee Performance: Systematic Literature Review - Ginting, Josafat Gracia; Ahmad Rais Habib S; Muh Nurfadel Hamzah; Ridfan Rifadly Abadi (Jurnal Multidisiplin Sahombu, 2025)
Employee performance plays a crucial role in an organization success, and employee mental health is a key factor that can influence performance stability. This study aims to systematically synthesize literature on how mental health affects employee performance. The research method is a Systematic Literature Review (SLR). This study analyzed 30 articles selected from the Google Scholar and Crossref databases for the period 2021–2025 using the Publish or Perish 8 software. The selection process followed the PRISMA protocol. The results of this study show several main findings, namely; (1) mental health mediates the relationship between depression, anxiety and work stress on performance; (2) mental health can encourage productive and innovative behavior which then increases work engagement; (3) mental health is a factor that strongly influences turnover; (4) Mental health has a positive and significant effect on job satisfaction; (5) mental health is a key factor in maintaining employee emotional stability in order to increase employee productivity; and (6) mental health can mediate leadership and a supportive work environment on employee productivity.